2018
DOI: 10.2147/ott.s181842
|View full text |Cite
|
Sign up to set email alerts
|

Clinical evaluation of vascular normalization induced by recombinant human endostatin in nasopharyngeal carcinoma via dynamic contrast-enhanced ultrasonography

Abstract: BackgroundThe present study confirmed the presence and exact range of “vascular normalization window” induced by recombinant human endostatin (RHES) in patients with nasopharyngeal carcinoma (NPC) by analyzing the variation of dynamic contrast-enhanced ultrasonography (DCE-US) quantitative parameters. Also, the clinical application of DCE-US in the evaluation of vascular normalization was assessed.Materials and methodsA total of 30 previously untreated patients with stage III–IVA NPC were enrolled in the prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Due to their vascular abnormality, tumors are known to have impaired blood perfusion and offer resistance to chemotherapy [ 7 ]. Endostatin has been used to normalize the aberrant vasculature in tumors [ 52 ] and this effect has even been explored in clinical settings [ 53 ]. In combination with doxorubicin, endostatin has been shown significant tumor and metastasis inhibition in mice 4T1 breast cancer [ 54 ].…”
Section: Resultsmentioning
confidence: 99%
“…Due to their vascular abnormality, tumors are known to have impaired blood perfusion and offer resistance to chemotherapy [ 7 ]. Endostatin has been used to normalize the aberrant vasculature in tumors [ 52 ] and this effect has even been explored in clinical settings [ 53 ]. In combination with doxorubicin, endostatin has been shown significant tumor and metastasis inhibition in mice 4T1 breast cancer [ 54 ].…”
Section: Resultsmentioning
confidence: 99%
“…Since then, scholars have reported through clinical experience and empirical evidence that RHES + radiotherapy and/or chemotherapy has an effect superior to that of a single treatment on various malignant tumors, such as metastatic melanoma and gastric cancer [23,24]. In the clinical treatment of patients with NPC, the RHES + IMRT treatment has also shown good therapeutic effects and good safety [25]. In this study, we focused on 65 patients with NPC having undergone RHES + CCRT, among whom 41 (63.0%) were allocated to the responder group and 24 to the non-responder group.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, new effective therapeutic schemes and sensitive evaluation of curative effect by noninvasive imaging methods become very important. In addition to conventional chemotherapy combinations, multiple trials of anti-angiogenic therapy with anti-VEGF (bevacizumab), anti-VEGFR (sorafenib, Axitinib) or for pancreatic cancer, have been carried out with different results, some producing additional bene ts [41][42][43]and others didn't [16][17][18][19][20][21] with different therapies. In our study, Endostar was chosen as an antiangiogenic drug for the treatment of pancreatic tumors on mouse pancreatic cancer xenografts alone or combined with Gemcitabine .…”
Section: Discussionmentioning
confidence: 99%
“…They reported that following administration of the antiangiogenic agents, a unique "window" occurred, where irregular vessels inside the tumor were normalized. In recent years, it has been reported that Endostar can not only inhibit neovascularization, but also induce pathological vascular normalization which has shown great clinical potential for enhancing effective drug delivery, improving local immunosuppressive microenvironment, and reducing distant metastasis [51][52]. Therefore, Endostar may be a potential drug for anti-angiogenic therapy of pancreatic cancer.…”
Section: Discussionmentioning
confidence: 99%